Pengembangan Sistem Informasi Inventarisasi Sarana dan Prasarana Non IT di STIKI Malang - Sa’i, Melanaumi Apriza Fahira; Prastiningtyas, Diah Arifah; Isyriyah, Laila (J-INTECH (Journal of Information and Technology), 2022)
BAUK is one of the work units at STIKI Malang which has the duty and authority to manage the inventory activities of non-IT facilities and infrastructure at STIKI Malang. Inventory must be carried out to ensure the quality, existence and management process of thousands of inventories in an institution. Previous research couldn’t be implemented due to differences in Inventory SOP and the lack of features made. The Information System for Inventorying Non-IT Facilities and Infrastructure at STIKI Malang which is currently being developed can record inventory faster and be able to display the latest accurate data, and provide features that are in accordance with the SOP for Inventorying the BAUK unit. The Information System for Inventorying Non-IT Facilities and Infrastructure at STIKI Malang is also equipped with features that can assist the BAUK unit in making decisions regarding the inventory process at STIKI Malang. With a research and development research method approach, this information system provides a broader development with updated features and services that are in line with the current needs of the BAUK unit inventory business process. The developments that have been carried out have resulted in new features and services that can help overcome existing problems in the BAUK unit, making it easier for the BAUK unit to carry out the inventory process at STIKI Malang.